Delay improves performance on a haptic spatial matching task - Zuidhoek, Sander; Kappers, Astrid M. L.; van der Lubbe, Rob H. J.; Postma, Albert (Experimental brain research, 2003)
Systematic deviations occur when blindfolded subjects set a test bar parallel to a reference bar in the horizontal plane using haptic information (Kappers and Koenderink 1999, Perception 28:781-795; Kappers 1999, Perception 28:1001-1012). These deviations are assumed to reflect the use of a combination of a biasing egocentric reference frame and an allocentric, more cognitive one (Kappers 2002, Acta Psychol 109:25-40). In two experiments, we have examined the effect of delay between the perception of a reference bar and the parallel setting of a test bar. In both experiments a 10-s delay improved performance. The improvement increased with a larger horizontal (left-right) distance between the bars. This improvement was interpreted as a shift from the egocentric towards the allocentric reference frame during the delay period.